Assessment of thermal comfort of frail people in a sitting posture under non-uniform conditions using a thermal manikin - El akili, Zoubayre; Bouzidi, Youcef; Merabtine, Abdelatif; Polidori, Guillaume; Kauffmann, Julien (Building and Environment, 2022)
Thermal comfort has gradually become an important research field in the context of sustainable living. Several thermal comfort studies have been conducted in thermally uniform environments, though far fewer are being performed in non-uniform thermal conditions. Recently, the evaluation of thermal responses in non-uniform thermal environments, has come to the attention of researchers. This study aims to evaluate the thermal responses of frail people using a “Newton” thermal manikin and a test chamber. Personalized cooling and heating floor systems were used to produce non-uniform conditions by supplying global cooling air flow and vertical heat flow to the whole manikin body. In this paper, skin temperature, core temperature, and thermal responses were examined and discussed in both males and females. The analysis showed a significant difference in thermal sensation and dynamic thermal sensation between females and males over time, and under the same experimental conditions. On the other hand, the ANOVA analysis revealed a significant difference in the main effect of gender in terms of thermal comfort. Results show that thermal discomfort in frail people originated largely from air temperature. It was found that air temperature increments of 5 °C–30 °C can modify thermal comfort by 1.5 scale units’ in comparison with the thermal sensation.
Keywords: Human thermoregulatory control; Overall thermal comfort; Overall thermal sensation; Thermal manikin